Features of the land plot as an object of mortgage relations: theoretical and practical aspects - Tsvigun, Iryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article deals with the features of mortgage relations, the object of which is a land plot. The existing national legislation and scientific researches on the chosen problem are analyzed. Strong conclusions and suggestions are made that have both theoretical and practical significance in the context of the study of the land plot as an object of mortgage relations